The Use of Stereotypes within South African Television Car Advertising using the German Language: A Multimodal Social Semiotic Approach. - Schafli, Sasha-Lee; Weber, Undine Susanne (Stellenbosch Papers in Linguistics Plus, 2023)
The use of German is a rare phenomenon in the South African television car advertising context, and thus seems to have a specific purpose. In this paper, through a social semiotic approach, we examine the use and function of German and South African national, gender and occupational stereotypes portrayed within SA car television advertisements that use the German language. It highlights how consumers use stereotypes to orientate themselves in a complex environment. We argue that the understanding of how stereotypes are conveyed through language use in combination with the visual portrayal of social actors presents insights into what German car advertising agencies may consider effective and appropriate advertising.